PENEGAKAN HUKUM DALAM KASUS TINDAK PIDANA PERKOSAAN TERHADAP PENYANDANG DISABILITAS SENSORIK YANG MENJADI KORBAN - Astuti, Laras; Setiautami, Nabilla (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Many cases of rape are not only committed by strangers but also by people close to them, including people with sensory disabilities. The limitations of people with sensory disabilities make it difficult for them to protect themselves or even fight the perpetrators. Based on this, this paper is written with the aim of discussing further about law enforcement in cases of rape against people with sensory disabilities who are victims. The research was conducted using a normative research method that focuses on secondary data and is supported by primary data from interviews with several sources. The data collected will be analyzed systematically and logically to be processed to obtain a brief overview. Based on the results of the study, it can be concluded that law enforcement against people with sensory disabilities who are victims of rape is still guided by the Criminal Procedure Code by paying attention to the provisions in the Law on Persons with Disabilities and adjusted to the needs of the victim.